Biomarker-based risk assessment of dietary intervention in patients with coronary artery disease during cardiac rehabilitation: a quasi-experimental study - Kotewitsch, Mona; Scharnagl, Hubert; Köstler, Dennis; Teschler, Marc; Garbsch, René; Schäfer, Hendrik; Waranski, Melina; Vereckei, Katalin; Böll, Gereon; Kleber, Marcus E.; Dressel, Alexander; März, Winfried; et al. (Frontiers in nutrition, 2025)
Background and aimsCardiac rehabilitation (CR) is integral to secondary prevention in coronary artery disease (CAD), incorporating exercise, medical optimization, and dietary interventions. While low-carbohydrate (low-carb) and low-fat diets may improve metabolic health, their comparative impact on cardiovascular risk in CR remains unclear. This study assessed the effects of low-carb and low-fat diets on cardiovascular risk, body composition, and major adverse cardiovascular and cerebrovascular events (MACCE) in CAD patients undergoing inpatient CR.MethodsIn this quasi-experimental study, 313 CAD patients (56 ± 7 years, 20% women) participated in CR, adopting a low-carb (n = 58), low-fat (n = 136), or regular diet (n = 119, control). Dietary assignment was non-randomized and based on assisted patient self-selection. A biomarker-based score to estimate the 10-year cardiovascular mortality risk, bioelectrical impedance analysis, and laboratory parameters (HbA1c, lipids, inflammation markers) were assessed at baseline, discharge, and 6-month follow-up. Kaplan-Meier analysis was used to compare MACCE recorded for a mean of 470 ± 293 days.ResultsDuring 3-4 weeks of CR, the 10-year cardiovascular mortality risk decreased by a mean of 3.7 ± 9.6%, with no difference between dietary groups (p = 0.8651). HbA1c improved in the low-carb group during CR compared to the low-fat and regular diet (−4.0 ± 6.6%), but the effect was not significant after adjustments for baseline HbA1c, diabetes prevalence, and medication (p = 0.168). Reductions in BMI, body fat, and visceral fat were recorded in the low-carb and low-fat group, compared to the control group (p ≤ 0.0001). Total cholesterol, LDL, and triglyceride levels also decreased in all groups during CR without significant differences (p ≥ 0.3957). MACCE incidence did not differ between the groups (p = 0.2).ConclusionNo additional immediate benefit in risk reduction during CR for low-carb or low-fat dietary interventions was detected. However, the low-fat and low-carb diet resulted in significantly greater reductions in BMI, body fat and visceral fat, with a tendency towards more stable effects over 6 months in the low-fat group. While glycemic control was improved in the low-carb group during inpatient CR, long-term adherence appeared challenging, particularly for diabetic patients as HbA1c levels re-increased during 6 months follow-up. Since no difference in MACCE was seen, the dietary interventions may be considered equally safe for CAD patients.
Gesehen am 10.12.2025